TINGKAT PENGETAHUAN MAHASISWI DIII KEBIDANAN STIKes PEKANBARU MEDICAL CENTER TENTANG HIV/AIDS - Richa Rahmana, Fatma; Wulan, Retno; Desriva, Nia; Purwani Sari, Endah; Agnes lexi, Sri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
According to AEM modeling data in 2021, it was estimated that around 526,841 people were living with HIV with an estimated 27 000 new cases. Approximately, 40 percent of these new infections occurred in women. The causes vary, including the COVID-19 pandemic, low ARV treatment retention, inequality in HIV services and ongoing stigma and discrimination stemming from a lack of public knowledge about HIV-AIDS. Strengthening the triple 95 strategy is being pursued by intensifying health promotion, preventing high-risk behaviors, case detection (screening, testing, tracing), and case management. Additionally, the Ministry of Health has included HIV-AIDS control strategies as part of the Minimum Service Standards in Health Facilities. This strategy is outlined in the Minister of Health Regulation Number 4 of 2019 concerning Technical Quality Standards for Basic Services in the Minimum Standards for Health Services. Efforts are made not only for women, children, and adolescents but also for all life cycles, from newborns, toddlers, primary school-aged children, teenagers, adults, to the elderly.The purpose of this study is to assess the knowledge of DIII Midwifery students at STIKes PMC Pekanbaru about HIV/AIDS. This research is descriptive. The sampling technique used was accidental sampling with a sample size of 34 people. The tool used for sampling was a questionnaire with univariate analysis. The frequency distribution of respondents' knowledge about HIV/AIDS showed that 21 respondents (61.7%) had good knowledge, 9 respondents (26.5%) had fairly good knowledge, and 4 respondents (11.7%) had poor knowledge. It is hoped that the DIII Midwifery students at STIKes PMC Pekanbaru can support the government's program by raising awareness about the dangers of HIV/AIDS in their surroundings, thereby helping the government in combating HIV/AIDS. Keywords:Knowledge, HIV, AIDS.